Online assessment of risk factors for dementia and cognitive function in healthy adults. (27th September 2017) - Huntley, J.; Corbett, A.; Wesnes, K.; Brooker, H.; Stenton, R.; Hampshire, A.; Ballard, C.
Abstract : Objective: Several potentially modifiable risk factors for cognitive decline and dementia have been identified, including low educational attainment, smoking, diabetes, physical inactivity, hypertension, midlife obesity, depression, and perceived social isolation. Managing these risk factors in late midlife and older age may help reduce the risk of dementia; however, it is unclear whether these factors also relate to cognitive performance in older individuals without dementia. Method: Data from 14 201 non‐demented individuals aged >50 years who enrolled in the online PROTECT study were used to examine the relationship between cognitive function and known modifiable risk factors for dementia. Multivariate regression analyses were conducted on 4 cognitive outcomes assessing verbal and spatial working memory, visual episodic memory, and verbal reasoning. Results: Increasing age was associated with reduced performance across all tasks. Higher educational achievement, the presence of a close confiding relationship, and moderate alcohol intake were associated with benefits across all 4 cognitive tasks, and exercise was associated with better performance on verbal reasoning and verbal working memory tasks. A diagnosis of depression was negatively associated with performance on visual episodic memory and working memory tasks, whereas being underweight negatively affected performance on all tasks apart from verbal working memory. A history of stroke was negatively associated with verbal reasoning and working memory performance. Conclusion: Known modifiable risk factors for dementia are associated with cognitive performance in non‐demented individuals in late midlife and older age. This provides further support for public health interventions that seek to manage these risk factors across the lifespan.